Biological heterogeneity in ADNI amnestic MCI - Nettiksimmons, Jasmine (2014)
BACKGROUND: Previous work examining normal controls from the Alzheimer's Disease Neuroimaging Initiative (ADNI) identified substantial biological heterogeneity. We hypothesized that ADNI mild cognitive impairment (MCI) subjects would also exhibit heterogeneity with possible clinical implications. METHODS: 138 ADNI subjects diagnosed with amnestic MCI were clustered based on baseline MRI, cerebrospinal fluid, and serum biomarkers. The clusters were compared with respect to longitudinal atrophy, cognitive trajectory, and time to conversion. RESULTS: Four clusters emerged with distinct biomarker patterns: The first cluster was biologically similar to normal controls and rarely converted to Alzheimer's disease (AD) during follow-up. The second cluster had characteristics of early Alzheimer’s pathology. The third cluster showed the most severe atrophy but barely abnormal tau levels and a substantial proportion converted to clinical AD. The fourth cluster appeared to be pre-AD and nearly all converted to AD. CONCLUSIONS: Subjects with MCI who were clinically similar showed substantial heterogeneity in biomarkers.